Hyperparathyroidism due to Parathyroid Adenoma with Co-existing Vitamin D Deficiency A Case Report (BIRDEM Medical Journal, 2016)
Primary hyperparathyroidism is often asymptomatic, may be detected during routine investigations or may present with features of hypercalcaemia. Vitamin D deficiency causing secondary hyperparathyroidism presents with musculoskeletal symptoms. Studies have shown an association between primary hyperparathyroidism and vitamin D deficiency. It has also been observed that when co-exist, these two conditions contribute to each others disease presentation and severity. This case report depicts initial asymptomatic hyperparathyroidism developing symptoms due to co-existing parathyroid adenoma and vitamin D deficiency in a 26-year-old muslim Bangladeshi female who responded well to adequate pre, per and post parathyroidectomy medical managementBirdem Med J 2015; 5(2): 104-106